Special Structure under the Federal System of Nepal - Shrestha, Milan (KMC Research Journal, 2025)
The present constitution of Nepal formally endorsed federal system by restructuring the state as per spirit of the Interim Constitution. Under the federal system, the constitution provisioned to have main structure – the federation, the provinces and the local levels for political powers and special structure – special, protected and autonomous regions for economic development, social and cultural preservation. The main structures have already been constituted, while the special structures have not yet been implemented. Neither constitution nor the federal law included a list of powers for special structures. There seems to be still confusion and problems regarding the forms and powers of the special structure in the federal system of Nepal. This paper explores on the foundation of debate on special structure and discusses the constitutional and legal provisions on special structure. Based on interpretative paradigm, the author used both primary and secondary information to write this paper. Descriptive and analytical methods have been adopted for the analysis and presentation of provisions on special structures. The constitution did not incorporate special structures as recommended by the CA Committee and State Restructuring Commission, any powers and authority under the constitution are not given to special structures. It is necessary to implement the constitutional provisions on special structure in order to full-fledged implementation of the constitution. The paper highlights the need for a special structure for diversity management, in a context where only the main structure under traditional federalism is studied. It also discusses on the justification for a special structure in the federal system and the constitutional and legal provisions in this regard from a new perspective.